PERAN LATAR BELAKANG PENDIDIKAN SEBAGAI VARIABEL MODERASI PADA PENGARUH PENGETAHUAN AKUNTANSI TERHADAP PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM: Nurapni Jami Putri, Cyntia Carolina - JamiPutri, Nurapni; Carolina, Cyntia (LPPM STIA Nusantara Sakti, 2023)
This research aims to analyze the influence of accounting knowledge moderated by educational background on the preparation of financial reports based on SAK EMKM in Sungai Banyak City MSMEs. The analysis technique in this research uses linear regression analysis with moderating variables. Based on the results of the research, it shows that accounting knowledge has a significant effect on the preparation of financial reports based on SAK EMKM in MSMEs in Sungai Banyak City with a significance level of 0.010 (<0.05). The role of educational background strengthens the moderating relationship between accounting knowledge and the preparation of financial reports based on SAK EMKM.